A flexible solid-state electrolyte for wide-scale integration of rechargeable zinc–air batteries. Issue 2 (4th January 2016) - Fu, Jing; Zhang, Jing; Song, Xueping; Zarrin, Hadis; Tian, Xiaofei; Qiao, Jinli; Rasen, Lathanken; Li, Kecheng; Chen, Zhongwei
Abstract : Replacing liquid electrolytes with a versatile, solid-state membrane based on highly functionalized cellulose nanofibers allows for easy integration of rechargeable zinc–air into any bendable and wearable devices. Abstract : Rechargeable zinc–air batteries, having high energy densities and cost-effectiveness, are important environmentally-benign energy storage solutions. Here we developed a facile strategy for fabricating a nanoporous alkaline-exchange electrolyte membrane from natural cellulose nanofibres, exhibiting high ionic-conductivity and water retention as well as high bending flexibility. These advantages render the membrane a promising solid-state electrolyte for rechargeable zinc–air batteries in lightweight and flexible electronic applications.